Specific aspects of Russian national cross-country skiing team training for 2014 Olympics - Knyazev, A. P.; Vinogradov, L. M.; Perevozchikov, O. O. (Theory and Practice of Physical Culture, 2017)
Objective of the study was to analyse the key aspects of the modern training systems applied by the strongest Russian ski racers. Methods and structure of the study. The study was designed to analyse the key aspects of the athletic training systems including training days; applied training tools; volume and intensity of physical loads; load distribution by intensity zones; competitive performance management for two pre-seasons; some aspects of the training system individualization for every elite athlete; and middle-altitude training and competitive process analysis. Study results and discussion. Physical load volumes profiled by the key training elements comprise one of the most important characteristics of a training system. For instance, the authors analysed the load volumes by the key training elements (run race, roller sking, ski race, jump simulation, stregth training) applied by the Russian national team members in the season of 2013/2014. Conclusion. The study reports the key aspects of the Russian national cross-country skiing team training for the top-ranking event of the 2014 season including the following: competitive environment modelling (distance, terrain of the track, snow conditions, air temperatures, sport equipment etc.); the key cyclic training loads were reduced in the pre-Olympic period by 12-15% versus the previous years; the top sport shape was reached in the World Cup events i.e. using the events for the final conditioning purposes; the training process was duly customized to the individual style- and distance-related preferences of the athletes; the middle-altitude training days were increased by 40%; the final pre-season training session took place at the 2320 m altitude that was much higher than the competitive one (1430 m); the strength training was stepped up in the pre-season by the maximum-effort practices and static/dynamic exercises; and the physical loads were strictly managed in the training process.